2007
DOI: 10.1073/pnas.0608299104
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II deprivation impairs CD4 T cell motility and responsiveness to antigen-bearing dendritic cells in vivo

Abstract: The role continuous contact with self-peptide/MHC molecules (self ligands) in the periphery plays in the function of mature T cells remains unclear. Here, we elucidate a role for MHC class II molecules in T cell trafficking and antigen responsiveness in vivo. We find that naïve CD4 T cells deprived of MHC class II molecules demonstrate a progressive and profound defect in motility (measured by real-time two-photon imaging) and that these cells have a decreased ability to interact with limiting numbers of cogna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
2
4

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 51 publications
(64 reference statements)
7
67
2
4
Order By: Relevance
“…Recently, it was shown that basal activation of Rac1 via MHC class II molecule stimulation is essential for CD4 ϩ T-cell motility, and self-ligand deprivation is associated with reduced levels of active Rac1 (47). In the present study, enhanced Rac1 GTP binding activity in CD4…”
Section: Discussionsupporting
confidence: 59%
“…Recently, it was shown that basal activation of Rac1 via MHC class II molecule stimulation is essential for CD4 ϩ T-cell motility, and self-ligand deprivation is associated with reduced levels of active Rac1 (47). In the present study, enhanced Rac1 GTP binding activity in CD4…”
Section: Discussionsupporting
confidence: 59%
“…There are conflicting data regarding loss of MHC and T cell reactivity (reviewed in [33]). Several reports indicate that self-interactions (TCR-MHC) maintain a high threshold for self-antigens [27;28;30;33], whereas others show that these interactions promote modest receptor clustering and CD3ζ chain phosphorylation [20;32] and in the case of CD4 cells, MHC class II availability promotes activation of Rap1 and Rac1, enhancing motility [65], suggesting self-interactions are responsible for partial activation that sensitizes the TCR as well as for increasing the potential for these cells to encounter and respond to antigen. One possibility that remains to be explored is that quantum signaling through the TCR might be responsible for sensitization and for tuning in T cells with varying avidity for self-peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Several microbial products, such as lipopolysaccharide and CpG DNA, have recently been reported to induce dendritic cell (DC) maturation by binding to TLR family molecules, including TLR-5 (16,20,32,52). DCs are found in physical contact with naive T cells in vivo (12,63). Consequently, DCs recognize microbial products and activate antigen-specific T-cell clonal expansion.…”
Section: Flagellin Stimulates Enhanced Virus Neutralization and Hi Acmentioning
confidence: 99%